Предмет: Алгебра,
автор: Aнькa170702
Решить уравнение x^3-27-3x(x-3)=0!
Ответы
Автор ответа:
0
x^3-27-3x(x-3)=0
x^3-27-3x^2+9x=0
(x^3-3x^2)-(9x-27)=0
x^2(x-3)-9(x-3)=0
(x^2-9)(x-3)=0
x=+-3 x=3
Ответ:+-3;3
x^3-27-3x^2+9x=0
(x^3-3x^2)-(9x-27)=0
x^2(x-3)-9(x-3)=0
(x^2-9)(x-3)=0
x=+-3 x=3
Ответ:+-3;3
Похожие вопросы
Предмет: История,
автор: Аноним
Предмет: Русский язык,
автор: Аноним
Предмет: Литература,
автор: ajdarhanmakaev2
Предмет: Математика,
автор: linagolovko83
Предмет: Математика,
автор: KeshaKesha